Pengaruh Faktor Internal dan Eksternal Terhadap Kinerja Keuangan Usaha Mikro Kecil dan Menengah (Umkm) Syari`Ah di Indonesia - Sihombing, Ammar Halomoan; Armayani, Reni Ria; Hasibuan, Fadli Hasbi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the influence of internal and external factors on the financial performance of Sharia-based Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The internal factors analyzed include managerial capabilities, operational efficiency, and compliance with Sharia principles. Meanwhile, external factors encompass government policy support, access to financing, and market dynamics. A quantitative approach was employed using multiple regression analysis based on survey data collected from Sharia MSME actors across several regions in Indonesia. The findings indicate that both internal and external factors significantly influence the financial performance of Sharia MSMEs, with internal factors having a more dominant role. These results provide valuable insights for formulating policies and strategies to enhance the competitiveness of Sharia-based MSMEs at the national level.